2011
DOI: 10.1097/01.pra.0000407963.26981.a6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Frequency of the Methylenetetrahydrofolate Reductase (MTHFR) C677T Polymorphism in Depressed Versus Nondepressed Patients

Abstract: Numerous studies have found an association between low serum folate levels and incidence of depression. Folic acid supplementation has been successfully used as an adjunct to treat depression in these patients. However, some individuals have a genetic deficiency in the methylene tetrahydrofolate reductase (MTHFR) gene that limits conversion of folic acid to its biologically active form, L-methylfolate. Several studies have identified a higher frequency of genetic variations in the MTHFR gene in depressed patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…It also seems likely that the common genetic variation C667T of the methylenetetrahydrofolate reductase (MTHFR) enzyme may impair the folic acid metabolism being responsible for low (<50%) levels of the active enzyme (Papakostas et al, 2012). This mutation has been shown to be overrepresented among depressive patients (Almeida et al, 2008;Gilbody, Lewis, & Lightfoot, 2007) and should be taken into account when identifying patients in need for treatment (Coppen & Bolander-Gouaille, 2005;Lizer, Bogdan, & Kidd, 2011). Lastly, it has recently been suggested that the L-methylfolate formation of folate may be more bioavailable as it enters the one carbon cycle after the step where MTHFR is needed; therefore, it should be administered instead of folic acid, especially in patients with this genetic variation as well as in those taking specific other medication or consuming alcohol.…”
Section: Discussionmentioning
confidence: 98%
“…It also seems likely that the common genetic variation C667T of the methylenetetrahydrofolate reductase (MTHFR) enzyme may impair the folic acid metabolism being responsible for low (<50%) levels of the active enzyme (Papakostas et al, 2012). This mutation has been shown to be overrepresented among depressive patients (Almeida et al, 2008;Gilbody, Lewis, & Lightfoot, 2007) and should be taken into account when identifying patients in need for treatment (Coppen & Bolander-Gouaille, 2005;Lizer, Bogdan, & Kidd, 2011). Lastly, it has recently been suggested that the L-methylfolate formation of folate may be more bioavailable as it enters the one carbon cycle after the step where MTHFR is needed; therefore, it should be administered instead of folic acid, especially in patients with this genetic variation as well as in those taking specific other medication or consuming alcohol.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, C677T and A1298C SNPs have been strongly associated with decreased MTHFR activity (Frosst et al, 1995; der Put et al, 1998;Ulvik et al, 2007), controversial results have been found regarding their role in the genetic vulnerability to depression and in the final effects on blood folate levels (Moorthy et al, 2012;Wu et al, 2013;Zappacosta et al, 2014;Gatt et al, 2015). Regarding MTHFR C677T, several studies have shown an increased risk for MDD in T allele or TT genotype individuals (Arinami et al, 1997;Bjelland et al, 2003;Lewis et al, 2006;Shen et al, 2014), but numerous studies have not found significant associations (Kunugi et al, 1998;Hickie et al, 2001;Tan et al, 2004;Reif et al, 2005;Almeida et al, 2008;Gaysina et al, 2008;Hong et al, 2009;Lizer et al, 2011;Evinova et al, 2012;Lan et al, 2012;Lok et al, 2014). One study (Bousman et al, 2014) reported that bearing the 677CC genotype could increase an individual's probability of remaining depressed in the long term.…”
Section: Discussionmentioning
confidence: 95%
“…Folate deficiency has been also associated with Major Depressive Disorder (MDD) presumably because of its impact on neurotransmitter synthesis, which relies on the folate-dependent one-carbon pathway (Mischoulon and Raab, 2007). Moreover, studies showed that low folate levels may delay improvement in antidepressanttreated individuals, whereas folate supplementation may improve response to antidepressant drugs in MDD patients (Farah, 2009; gene has been widely investigated in association with MDD and its treatment with inconclusive findings (Lewis et al, 2006;Gaysina et al, 2008;Lanctot et al, 2010;Lizer et al, 2011;Mischoulon et al, 2012;Jamerson et al, 2013;Wu et al, 2013;Gatt et al, 2015). In particular, the two most commonly studied single nucleotide polymorphisms (SNPs) are rs1801133 (C677T) and rs1801131 (A1298C).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most extensively studied link is between low folate levels and depression, where an association has been demonstrated and a therapeutic role for folate has been proposed (Papakostas et al, 2012). Similarly to folate suboptimal blood values, MTHFR C677T polymorphism has been demonstrated to be associated with major depression (Lizer et al, 2011), schizophrenia (Zhang et al, 2013), and bipolar disorder (Rai, 2011)), being the magnitudes of the associations moderate but still statistically significant. Emerging evidence of an association with the MTHFR A1298C polymorphism was also found (Zhang et al, 2010).…”
Section: Relationship Between 510-mthfr Polymorphisms Folate Levelsmentioning
confidence: 95%